Calidad del servicio y satisfacción del cliente de Kentucky Fried Chicken en el Mall Aventura Iquitos 2024 - Rolando Flores, Piero (2025)
The present research had as its principal objective to analyze the relationship between customer satisfaction and service quality at Kentucky Fried Chicken (KFC), Iquitos location, during the year 2024. The study adopted a quantitative approach, with a descriptive-correlational scope and a non‑experimental, cross‑sectional design. The sample comprised 384 food customers at the Mall Aventura branch. A structured questionnaire served as the data‑collection instrument. The information gathered was processed using Microsoft Excel and IBM SPSS Statistics v25. The results revealed a Spearman correlation coefficient of 0.818, indicating a high, direct correlation between service quality and customer satisfaction. Accordingly, the alternative hypothesis (HI1) was accepted and the null hypothesis (H0) was rejected.